Assessing the Impact of Universal Primary Education Policy on Gender Equality in Education in Uganda - Kato Mukasa; Lydia Nakato Mirembe; Amina Nalule Kabugo (Research and Advances in Education, 2024)
This paper provides an in-depth analysis of the impact of Uganda’s Universal Primary Education (UPE) policy on gender equality in the realm of education. Since its inception in 1997, the UPE policy has been a cornerstone of Uganda’s educational reform, with the primary objective of offering free primary education to all children. A significant aspect of this policy has been its focus on enhancing female enrollment, in response to the historical underrepresentation of girls in education due to socio-economic, cultural, and infrastructural barriers. This study employs a comprehensive approach to assess the policy’s effectiveness in bridging the gender gap within Ugandan primary schools. By analyzing a variety of metrics, including enrollment rates, dropout rates, and academic performance, the paper aims to provide a nuanced understanding of the policy’s outcomes. The analysis extends beyond mere statistics to explore the qualitative aspects of the policy’s implementation, such as the provision of gender-sensitive facilities and teaching methods, which are crucial for sustaining girls’ participation in education. Furthermore, the paper examines the broader socio-economic context in which the UPE policy operates, considering factors such as poverty, child labor, and cultural norms that disproportionately affect girls’ access to education. By situating the policy within this context, the study highlights the complex interplay between educational policies and societal dynamics in shaping gender equality in education. This paper seeks to contribute to the ongoing discourse on gender equality in education by offering a comprehensive evaluation of the UPE policy’s impact on female enrollment and retention in Ugandan primary schools. Through this analysis, the paper aims to provide insights into the successes and challenges of the policy, thereby informing future efforts to achieve gender parity in education.